"Ecstasy" toxicity to adolescent rats following an acute low binge dose. Issue 1 (December 2016) - Teixeira-Gomes, Armanda; Costa, Vera; Feio-Azevedo, Rita; Duarte, José; Duarte-Araújo, Margarida; Fernandes, Eduarda; Bastos, Maria; Carvalho, Félix; Capela, João
Abstract Background 3, 4-Methylenedioxymethamphetamine (MDMA or "ecstasy") is a worldwide drug of abuse commonly used by adolescents. Most reports focus on MDMA's neurotoxicity and use high doses in adult animals, meanwhile studies in adolescents are scarce. We aimed to assess in rats the acute MDMA toxicity to the brain and peripheral organs using a binge dose scheme that tries to simulate human adolescent abuse. Methods Adolescent rats (postnatal day 40) received three 5 mg/kg doses of MDMA (estimated equivalent to two/three pills in a 50 kg adolescent), intraperitoneally, every 2 h, while controls received saline. After 24 h animal sacrifice took place and collection of brain areas (cerebellum, hippocampus, frontal cortex and striatum) and peripheral organs (liver, heart and kidneys) occurred. Results Significant hyperthermia was observed after the second and third MDMA doses, with mean increases of 1 °C as it occurs in the human scenario. MDMA promoted ATP levels fall in the frontal cortex. No brain oxidative stress-related changes were observed after MDMA. MDMA-treated rat organs revealed significant histological tissue alterations including vascular congestion, but no signs of apoptosis or necrosis were found, which was corroborated by the lack of changes in plasma biomarkers and tissue caspases. In peripheral organs, MDMA did not affect significantly protein carbonylation, glutathione, or ATP levels, but liver presented a higher vulnerability as MDMA promoted an increase in quinoprotein levels. Conclusions Adolescent rats exposed to a moderate MDMA dose, presented hyperthermia and acute tissue damage to peripheral organs without signs of brain oxidative stress.